Bacteriophage Technology and Modern Medicine - Aa Haeruman Azam; Xin-Ee Tan; Srivani Veeranarayanan; Kotaro Kiga; Longzhu Cui (MDPI AG, 2021)
The bacteriophage (or phage for short) has been used as an antibacterial agent for over a century but was abandoned in most countries after the discovery and broad use of antibiotics. The worldwide emergence and high prevalence of antimicrobial-resistant (AMR) bacteria have led to a revival of interest in the long-forgotten antibacterial therapy with phages (phage therapy) as an alternative approach to combatting AMR bacteria. The rapid progress recently made in molecular biology and genetic engineering has accelerated the generation of phage-related products with superior therapeutic potentials against bacterial infection. Nowadays, phage-based technology has been developed for many purposes, including those beyond the framework of antibacterial treatment, such as to suppress viruses by phages, gene therapy, vaccine development, etc. Here, we highlighted the current progress in phage engineering technology and its application in modern medicine.